SKIN AVILABLE MASTOID AREA ON THE STAGE OF ITS STRAIN - D.S. Avetikov; D.V. Steblovskii; I.I. Starchenko (Ukrainian Medical Stomatological Academy, 2016)
According to the latest statistics in the scientific journals abnormal scarring and negative results of plastic surgery occur in 5-6% of the total. Therefore, an optimal aesthetic scar and maximum results after cosmetic otoplasty are obtained and lower rhytidectomy remains a challenge in plastic and reconstructive surgery and rehabilitation. Objective: To investigate the morphological features skin-fat grafts mastoid areas at different stages of deformation. Materials and methods. The experiment used 25 skin-fat grafts, 5 of which stretched for 5, 10, 15, 20, 25 mm respectively. The processing of the results was carried out by conventional statistical methods In the study of microscopic skin preparations mastoid area stretching after a 5 mm are minimal, barely noticeable differences from intact skin respective anatomical site. Yes, clearly differentiated basal epidermis, ribbed, granular and horny layers, structural organization which are at rest. It should, however, note a slight increase in intraepithelial lymphocytes in basal and lower parts of the thorny layer, which occurs mainly in the peripheral parts of the skin graft, which in our opinion is a response to mechanical force. In the study of microscopic skin preparations of mastoid area stretching after a 10-mm change become more apparent compared to intact skin. In the epidermis manifestation of pathological processes less noticeable than in the dermis. Yet it should be noted that the increase in the treatment group in the thorny layer of cells with signs of hydropic degeneration, in some cases, there has been epitheliocytes piknotychne shrinkage nuclei. The described morphological pattern should be regarded as a pathological process involving a violation of trophic epithelial cells, which in turn may be due to mechanical action. In some cases, epithelial cells with degenerative were changed. The study of the structure of skin and fat flap after stretching a 15 mm demonstrates further aggravation of pathological processes, both in surface epithelium of the skin and in the dermis. Thus, in the experimental group that studied a thorny layer of the epidermis cells there is a progressive increase in the state hydropic degeneration, while some of them in cytoplasmic vacuoles with fluid, occupying almost the entire space of the cytoplasm. This morphological pattern indicative of the extent of extreme severity hydropic degeneration is the development of balloon degeneration, which is known to be a morphological equivalent focal necrosis. Also frequently in epitheliocytes piknotychni shriveled kernel was detected. The study of microscopic preparations of mastoid skin areas after stretching in the range of 20 mm and the emergence of a qualitatively new lesions in both the epidermis and the dermis can detect amplification. In particular, the epidermis, along with decrease in mitotic activity cambial cell elements, the cause of which was discussed earlier and expressed hydropic, in some cases balloon degeneration in the thorny layer of the epidermis, some changes were observed in the granular layer. The study of the structure of skin graft after stretching within 25 mm demonstrates serious pathological changes in most cases irreversible as the epidermis and dermis. The changes observed in the surface epithelium, largely resembled the results of tensile skin graft within 20 mm, however, a number of observations were more pronounced. However, the most significant changes we observed in the dermis. First of all, it should be noted polymorphism papillae, which was more pronounced than in preparations with less strain outside. Also, significant length of areas in which the boundary between the epidermis and dermis by a pronounced flattening of papillae looked like almost equal lines were proved.